(untitled) (Economic and Political Thought, 2018)
A comment is made in the introduction to the article that the low rate of investment observed for years and being far below the EU average is the main barrier to the development of Poland’s economy. The author believes that this disadvantageous trend may change as a result of the debt instruments market ‘Catalyst’ established in 2009. With the Catalyst market, on the one hand, an opportunity for development of funding economic undertakings with the use of bonds and, on the other hand, favourable and flexible investment of financial means in debt securities by a bigger number of corporate and individual investors emerged. In the article, attention is focused on corporate bonds, which, in the author’s opinion, due to advantages presented in the article, may constitute the most flexible and efficient source of funding businesses, which is an alternative to a bank debt.